Total Knee Arthroplasty Outcomes in Patients with Medicare, Medicare Advantage, and Commercial Insurance - Starring, Hunter; Waddell, William H.; Steward, William; Schexnayder, Stuart; McKay, Jack; Leonardi, Claudia; Bronstone, Amy; Dasa, Vinod (The Journal of Knee Surgery, 2019)
As more commercial insurance companies adopt a bundled reimbursement model, similar to the Comprehensive Care for Joint Replacement (CJR) algorithm for Medicare beneficiaries, accurate risk adjustment of patient-reported outcomes (PROs) is critical to ensure success. With this movement toward bundled reimbursement, it is unknown if a formula adjusting for similar risks in the Medicare population could be applied to PROs in commercially insured and Medicare Advantage populations undergoing total knee arthroplasty (TKA). This study was performed to compare PROs after TKA in these insurance groups after adjusting for proposed risks. Demographics and clinical data were abstracted from medical records of 302 patients who underwent TKA performed by a single surgeon at a university-based orthopaedic practice during 2013 to 2017. Differences in PROs between commercially insured, Medicare Advantage, and Medicare patients during the 6 months following surgery were evaluated while controlling for demographics, clinical data, and baseline PRO scores. Medicare and Medicare Advantage patients were older (p < 0.001) and had more comorbidities (p = 0.001) than commercial patients. During the first 3 months following TKA, patients in all three groups experienced similar rates of recovery. At 6 months after surgery, outcomes began to diverge by insurance group. Medicare patients reported significantly less ability to perform activities of daily living (78.6 vs. 63.2; p = 0.001), worse physical function (39.6 vs. 44.9; p = 0.003), and more pain interference (57.9 vs. 52.4; p = 0.018) at day 180 than commercially insured patients. There were no statistically significant differences between Medicare Advantage patients and either commercially insured or Medicare patients. Therefore, commercial insurance companies that intend to apply a risk-adjusted equation similar to the CJR algorithm to commercial populations should be cautioned since the postoperative outcomes in this investigation differed after adjusting for the same risk factors that have been proposed for inclusion in the CJR algorithm. Nonetheless, further studies should be performed to ensure that companies participating in bundled reimbursement models have a positive influence on comprehensive health care for patients and providers. This is a level III, retrospective prognostic study
Keywords: arthroplasty; knee; outcomes; insurance